In Vivo Antitumor Activity of Metal Silver and Silver Nanoparticles in the L5178Y-R Murine Lymphoma Model - Lara González, José Horacio; Gómez Flores, Ricardo Alberto; Tamez Guerra, Patricia; Monreal Cuevas, Enriqueta; Tamez Guerra, Reyes Silvestre; Rodríguez Padilla, María Cristina (Sciencedomain International, 2013)
Aims: To evaluate the antitumor potential of metal silver and polyvinilpyrrolidone nanoparticle-encapsulated silver on L5178Y-R murine lymphoma cell growth and survival of tumor-bearing mice. Study Design: In vitro and in vivo (pre-clinical) study. Place and Duration of Study: Universidad Autónoma de Nuevo León, Facultad de Ciencias Biológicas, Departamento de Microbiología e Inmunología, San Nicolás de los Garza, N.L., México, from January 2009 to December 2011. Methodology: Concentration-response cell viability assay was performed in vitro and mice survival studies were done using a L5178Y-R tumor-bearing mouse model. The PROBIT regression analysis was performed to determine the in vitro LC50. In vivo survival distributions were calculated by Kaplan-Meier and Cutler-Ederer analysis, and survival curves comparisons and hypothesis testing was done using the log-rank method. Results: Metal silver induced up to 100% L5178Y-R cells cytotoxicity, with an LC50 of 1.8 X 10-8 M, whereas silver nanoparticles caused up to 78% cytotoxicity, with an LC50 of 14.4 X 10-8 M. In addition, Intramuscular administration of metal silver and silver nanoparticles administered at the time of tumor injection significantly (P = .05) increased mice survival, where 70% and 60% of mice survived at day 35 respectively, as compared with such treatments administered 7 days after tumor induction (55% and 25% survival respectively); vincristine treatment caused 50% mice survival and tumor-bearing control mice had 20% survival. These results open further approaches on treating several types of cancer using free and nanoparticle-encapsulated silver-based therapies.